Asia’s emergence in cancer immunotherapy: challenges and opportunities - Yan Li; Bernard A Fox; Cheng Sun; Joe Yeong (Journal for ImmunoTherapy of Cancer)
Asia’s role in cancer immunotherapy research is rapidly expanding, driven by cutting-edge facilities, innovative technologies, and collaborative efforts. This commentary examines the region’s growing impact, highlighting key clinical trials, emerging research hubs, and unique challenges that we face. It discusses the need for standardization in cell and gene therapies, and more broadly all immunotherapies, addressing cost and accessibility issues. We examine the implications of genetic diversity in Asian populations as well as cultural and linguistic factors that affect clinical trials and patient care. The analysis extends to emerging opportunities in technological innovation and international collaboration, while addressing critical challenges in regulatory oversight, data transparency, and intellectual property protection. The success of the recent SITC-World Immunotherapy Council-Asia conference is showcased as a catalyst for future collaborations. By tackling these challenges and using innovations, Asian countries can significantly contribute to global advancements in cancer immunotherapy, potentially improving outcomes for patients worldwide.